Five little ducks and other action rhymes: walker books - Newcome, Zita (Walker London, 2002)
This picture book has over 25 lively action rhymes, including favourites like "I'm a Little Teapot" and "The Wheels on the Bus". Each is accompanied by step-by-step illustrations demonstrating the actions and is suitable for one child, or a whole group of children.